The Power of Connection: Discovering the Effects of Formal and Nonformal Environmental Education on Students’ Connectedness to Nature - Burgevin, Dylan; Haines, Sarah (Advances in Social Sciences Research Journal, 2025)
This study examined the relationship between students’ feeling of connectedness to nature (CN) and their exposure to environmental education (EE) experiences at formal or nonformal environmental education organizations. CN, often developed through EE programs, is a good predictor of environmentally responsible behavior (ERB) and is also an indicator of self-nature overlap. The Connectedness to Nature Scale Revised (CNS-R), and the Inclusion of Nature in Self (INS) surveys were administered at formal (N=3) and nonformal (N=3) environmental education organizations (EEOs), surveying students (N= 5,994) aged 7-14. Students participated in a range of program types including homeschool, summer camps, extended day, and overnight programs. Aggregated pretest and posttest survey data were analyzed to determine how students’ feelings of CN were affected by their EE experience and how these scores were influenced by age, duration, and frequency.